Heterogeneity of Glutamine Synthetase Polypeptides in Phaseolus vulgaris L. - Lara, Miguel (1984)
Glutamine synthetases from roots, nodules, and leaves of Phaseolus vulgaris L. have been purified to homogeneity and their polypeptide composition determined. The leaf enzyme is composed of six polypeptides. The cytosolic fraction contains two 43,000 dalton polypeptides and the chloroplastic enzyme is formed by four 45,000 dalton polypeptides. Root glutamine synthetase consists only of the same two polypeptides of 43,000 dalton that are present in the leaf enzyme. The nodule enzyme is formed by two polypeptides of 43,000 dalton, one is common to the leaf and root enzyme but the other is specific for N(2)-fixing nodule tissue. The two glutamine synthetase forms of the nodule contain a different proportion of the 43,000 dalton polypeptides.